IMPLEMENTASI KEBIJAKAN TENTANG PEKERJA ANAK DAN PENANGGULANGANNYA DI KOTA SEMARANG - Arif Wijaksono; Hartuti Purnaweni; Hesti Lestari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
Semarang as the capital of Central Java province opens opportunities for communities and areas including employment opportunities for young people to work or a chance to employ children. Child labor is not just children running jobs with wages, but once attached to the exploitation, hazardous work, delays in access to education and hinder the development and protection of the laws governing the physical, psychological and social development and the fulfillment of children's rights.The research was conducted in the city of Semarang. methods used in this research is descriptive-qualitative. The data was collected by using interviews, observations, and a review of the literature.This study aims to: first describe the implementation of child labor reduction policies in the city of Semarang, second, determine the factors that affect the success of the implementation of the policy response to child labor.The results showed that: The cooperation between government agencies is not good, the benefits of the implementation of the perceived lack of resources, lack of budget support, social, economic and family influence.Recommendation the authors provide recommendations: expand the range of services and the handling of child labor, building studios for children, need to budget specifications, provide skills for working children.